(untitled) (World Science, 2021)
Aim of study: to determine the pathogenetic factors that have an impact on the development of diabetic myopathy in children with DM1, to investigate the structure of the factors. The observation group included 136 children 14.3 ± 0.3 years old who have been suffering from DM1 for 1 to 10 years. Diagnosed diabetic myopathy in 45 (33.1%) patients (19 (24.4%) boys and 25 (44.8%) girls). By factor analysis, 5 factors were identified that are of leading importance in the pathogenesis of the development of diabetic myopathy in children with DM1. These factors accounted for 73.33% of the total dispersion. The first rank place was represented by the group factor (nitrotyrosine and homocysteine), which accounted for 19.54% of the total dispersion; interpreted as a factor of "oxidative stress". The second rank place was represented by the content of triglyceride in the blood serum and the level of the triglyceride-glucose complex, which amounted to 16.69% of the total dispersion; interpreted as "insulin resistance factor". The third rank place was interpreted as "the state of peripheral blood supply", which accounted for 13.93% of the total variance, and included the indicators of the ankle-brachial index before and after exercise stress. The fourth rank place was interpreted as an "anamnestic factor", which accounted for 12.04% of the total dispersion, and included three risk factors: age, sex of the patient, and duration of DM1. The fifth factor ("inflammation factor") included the indicators of glycosylated hemoglobin and interleukin-6, and demonstrates the development of chronic low-level inflammation against the background of hyperglycemia. Thus, using factor analysis, we determined that oxidative stress, insulin resistance, impaired peripheral circulation, duration of diabetes mellitus, female sex, chronic hyperglycemia, increased activity of proinflammatory cytokines had a priority effect on the pathogenesis of diabetic myopathy. We have formed a factorial model that will optimize the diagnosis of diabetic myopathy, improve approaches to its therapy and prevention, identifying among children with DM1 the risk group for the development and progression of this complication.